2006
DOI: 10.3748/wjg.v12.i8.1292
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between ultrasonographic and pathologic diagnosis of liver fibrosis due to chronic virus hepatitis

Abstract: INTRODUCTIONChronic hepatitis virus B or C infection results in damage to hepatocytes and may eventually lead to liver fibrosis, cirrhosis and/or hepatocellular carcinoma [1][2][3] . The diagnosis of liver fibrosis and cirrhosis in patients with chronic virus hepatitis is of therapeutic and prognostic importance.Although histologic examination of percutaneous biopsy specimens is the gold criterion for the severity of fibrosis and cirrhosis, biopsy is invasive and cannot be used repeatedly in follow-up. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 27 publications
2
44
0
1
Order By: Relevance
“…In our study, the portal vein diameter (D) was significantly enlarged at end-stage fibrosis patients, which is consistent with the reported data [31] . Walsh et al [29] found that hepatic artery blood flow (BF) and DPI are increased in CVH C patients at different fibrosis stages, while portal vein CI values remain unchanged.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In our study, the portal vein diameter (D) was significantly enlarged at end-stage fibrosis patients, which is consistent with the reported data [31] . Walsh et al [29] found that hepatic artery blood flow (BF) and DPI are increased in CVH C patients at different fibrosis stages, while portal vein CI values remain unchanged.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, spleen volume was increased in CVH and cirrhotic patients compared with the controls, which is consistent with the findings in other studies [19,20,22,[24][25][26][28][29][30][31]38] . It is well known that a relative interobser ver variability may limit the value for gray scale and Doppler ultrasonography [33][34][35][36] .…”
Section: Introductionsupporting
confidence: 93%
See 2 more Smart Citations
“…US can identify diffuse parenchymal disease, but cannot reliably distinguish fat from fibrosis. Some investigators rely on a single US parameter to detect early cirrhosis (Table 11) [91], while the others try to test single or combined US parameters to distinguish each stage of significant fibrosis (F2-F4; Table 12) [92]. The use of conventional US to distinguish fibrosis stages remains problematic.…”
Section: Liver Fibrosis Stagingmentioning
confidence: 99%